THE IMPROVEMENT OF POWER SYSTEM RELIABILITY WITH ENERGY STORAGE IN WIND GENERATION SYSTEM - Evtaleny Mauboy (Universitas Nusa Cendana, 2018)
The reasons to shift the generation system from conventional fuel oil generating system to clean energy sources are now based on the increase of fuel cost, climate change and environmental issues in reducing the greenhouse gas emission and also pollution. Wind is one of the renewable energy that has many advantages and the level of the penetration has increased now. Despite the abundance amount of wind, the fluctuation and the intermittent make wind generation system can affect the reliability of the power system. One of the solutions to the problems above is the use of electrical energy storage system. Power that stored in the electrical energy storage system can be used later when the wind is not strong enough to generate electric power. This research intends to investigate more on li-ion battery as one of the promising means in enhancing the reliability of power system when connecting to wind generation system in order to enhance the power system reliability. This work should contribute significantly in wind energy generation stability improvement with the storage system and there will be an advantage in battery storage system application. The results show the stability improvement of the simulation system connected to the wind generation with the battery.